2021
DOI: 10.3390/cancers13040646
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Hepatic Arterial Infusion Chemotherapy over Sorafenib in the Treatment of Locally Progressed Hepatocellular Carcinoma

Abstract: BACKROUND: Not all patients with hepatocellular carcinoma (HCC) benefit from treatment with molecular targeted agents such as sorafenib. We investigated whether New-FP (fine-powder cisplatin and 5-fluorouracil), a hepatic arterial infusion chemotherapy regimen, is more favorable than sorafenib as an initial treatment for locally progressed HCC. METHODS: To avoid selection bias, we corrected the data from different facilities that did or did not perform New-FP therapy. In total, 1709 consecutive patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The median survival time (MST) after propensity score was 15 months versus 7.9 months for the New-FP (n=442) and sorafenib groups (n=149), respectively (P<0.001). 113 Similarly, HAIC with low dose 5-FU and cisplatin (LFP) as a first-line treatment for HCC patients with PVTT (VP3, VP4) has also been proposed while switching to sorafenib if no response is observed. [114][115][116] The survival time in the HAIC (n=32) group was significantly longer versus the sorafenib (n=14) groups (309 days vs 120 days).…”
Section: Hepatic Arterial Infusion Chemotherapy (Haic)mentioning
confidence: 99%
“…The median survival time (MST) after propensity score was 15 months versus 7.9 months for the New-FP (n=442) and sorafenib groups (n=149), respectively (P<0.001). 113 Similarly, HAIC with low dose 5-FU and cisplatin (LFP) as a first-line treatment for HCC patients with PVTT (VP3, VP4) has also been proposed while switching to sorafenib if no response is observed. [114][115][116] The survival time in the HAIC (n=32) group was significantly longer versus the sorafenib (n=14) groups (309 days vs 120 days).…”
Section: Hepatic Arterial Infusion Chemotherapy (Haic)mentioning
confidence: 99%
“…In the present case, HAIC was selected as the first treatment at the time MVI was recognized. Several recent reports have demonstrated that HAIC has survival benefits compared with sorafenib, which had been a standard first-line systemic therapy, until the approval of atezolizumab plus bevacizumab, in patients with advanced disease with MVI without extrahepatic metastasis [27,28]. After discontinuation of HAIC, the patient moved on to lenvatinib, which was the standard systemic therapy like sorafenib at that time [24][25][26].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We describe a regimen for HAIC named "New FP" for the treatment of advanced HCC [19][20][21][22]. New FP is a regimen that consists of a fine-powder CDDP suspended with lipiodol and 5-FU.…”
Section: Introductionmentioning
confidence: 99%
“…New FP is a regimen that consists of a fine-powder CDDP suspended with lipiodol and 5-FU. We have previously reported the therapeutic outcomes of New FP in a single-center analysis and multi-center analysis [19,20,22]. Moreover, a non-randomized multi-center phase 2 trial of New FP and sorafenib in the treatment of HCC has also been reported [21].…”
Section: Introductionmentioning
confidence: 99%